The State and Economic Transformation: Toward an Analysis of the Conditions Underlying Effective Intervention - Rueschemeyer, Dietrich; Evans, Peter (Journal of Economic Sociology, 2011)
The paper presents a synthesis of key sociological insights regarding conditions underlining an effective state intervention into economy. It is focused on two main factors including the common coordinated bureaucracy and relative autonomy of the state from ruling class’s interests. The success of state intervention can be guaranteed neither by effective bureaucracy nor by the state autonomy. However comparative historical studies give an opportunity to reveal conditions under which these factors facilitate the state policy or put barriers to its implementation.